Diversity and abundance of insect visitors in four crops within a Costa Rican highland region - Gamboa-Barrantes, Nicole (2025)
Introduction: The interaction between plants and pollinators is vital for the reproduction of approximately 90% of angiosperms and directly affects ecosystems and agriculture. In tropical regions, 94% of plants require animal pollinators, and in Latin America, 58% of crops depend on pollination by insects. The stability and complexity of plant-pollinator interactions are influenced by several factors, such as floral morphology, which influences nectar accessibility and pollinator specialization. Objective: To compare the diversity and abundance of insect floral visitors in avocado, apple, plum, and blackberry crops in San Gerardo de Dota, Costa Rica. Methods: We systematically collected flower-visiting insects in these crops and identified them taxonomically to the lowest possible level. We then estimated alpha diversity for each crop and compared the community composition (beta diversity) of visiting insects among crops. Results: In 12 sampling visits, we collected a total of 2806 insects from 75 families across all four crops. Alpha diversity was greater in the avocado crop for all three indices (0D, 1D, and 2D). Apis mellifera was the most abundant species in all four crops, but Diptera was the most common group of visiting insects in avocado, particularly flies from the Syrphidae, Muscidae, Calliphoridae, Sarcophagidae, Sciaridae, and Tachinidae families. The insect community of the avocado crop was different from that of the apple, plum, and blackberry crops; however, the insect composition of the other crops was similar. Conclusions: The avocado crop is generalist in terms of floral visitors; this may be attributed to the size of the flower corolla, as flies with short mouthparts usually choose to feed on flowers with small corollas. Flowers of the other crops have similar morphology and are mainly visited by bees. The native entomofauna are abundant on the crop flowers, likely playing an important role as pollinators.